The Toxic Metal Arsenic Contamination of the Coastal Aquifers in the North Coast of Java, Indonesia - Chrisna Adhi Suryono (Universitas Diponegoro, 2015)
Pesatnya perkembangan industri dan aktivitas domestic di daerah pantai utara Jawa mendorong untuk perlunya dilakukan penelitian tentang kemungkinan adanya pencemaran logam Arsen (As) di akifer dangkal kota-kota Jakarta, Semarang dan Surabaya. Sebanyak 30 contoh air dari sumur-sumur yang berasal dari zona pemukiman di daerah pesisir dianalisis kandungan logam As dengan menggunakan teknik Atomic Absorption Spectrophotometer (AAS). Hasil analisis menunjukkan adanya kandungan logam As sebesar 59.65 μg L−1 di Jakarta. Rerata dan simpangan baku dari logam As di Jakarta, Semarang and Surabaya adalah 15.47 ± 18.79, 1.25 ± 2.05 and 0.59 ± 0.26 μgL-1. Terdapat korelasi yang nyata antara logam As dan Fe di airtanah. Dari hasil ini dapat disimpulkan bahwa tingkat kandungan logam As dan Fe di daerah akifer pantai utara Jawa masih berada di bawah ambang yang dipersyaratkan oleh Indonesian Drinking & Domestic Water Quality Standard for Ground Water and WHO’s (World Health Organization) Guideline Values for Drinking Water, kecuali untuk stasion 5 dan 6 dari Jakarta.Kata kunci: Arsen (As), AAS, akifer pantaiA study was conducted to assess the Arsenic (As) metal contamination of the shallow aquifers in Jakarta, Semarang, and Surabaya city of Java and its relation to the highly developed industrial and domestic activities in the coastal region. Arsen was assayed in the waters of 30 wells throughout the terrestrial cities, in residential zones using Atomic Absorption Spectrophotometer (AAS) technique. Analysis of the As level revealed that high As contents were found primarily in Jakarta, to a maximum of 59.65 μg L−1. The mean and standard deviation of As in Jakarta, Semarang and Surabaya were 15.47 ± 18.79, 1.25 ± 2.05 and 0.59 ± 0.26 μgL-1, respectively. The groundwater As concentration shows a correlation with Fe significantly. It was concluded that the levels of As in some investigated 3 Indonesian metropolis cities were below the maximum allowable concentrations of metals recommended by Indonesian Drinking & Domestic Water Quality Standard for Ground Water and WHO’s (World Health Organization)Guideline Values for Drinking Water, except for station 5 and 6 of Jakarta.Keywords: Arsenic (As), AAS, coastal aquifer